Síntese de WO3 e de heteroestruturas WO3/TiO2 pelo método de oxidação por peróxido e avaliação do potencial como fotocatalisadores - Castro, Isabela Alves de (2015)
The use of semiconductors for environmental applications and solar photoconversion has been widely explored recently. Due the intensive researches on renewable energy such as the photoelectrochemical H2 evolution from water splitting reaction, the design of new catalysts has been investigated. In this context, tungsten oxide – WO3 – is a promising catalyst for such application, however its conduction band is located at a more positive potential than the potential of water reduction, as a result WO3 does not have the ability to reduce H+ to H2. In the first part, this work deal with the synthesis of WO3 by the oxidant peroxide method, as a promising catalyst for this reaction. Tuning of the band-edge levels for the different synthesized catalysts was verified from Mott Schottky plot, and it represents the effective photoelectrocatalytic water splitting.In the second part, the study of heterostructuring TiO2 with WO3was investigated because of the possibility to mitigate the recombination of electron–hole pairs and therefore obtain more active systems for photocatalytic applications. The synthesis of WO3/TiO2 heterostructures was evaluated by hydrothermal method using three different routes: (I) precursors used as peroxo-complexes; (II) tungsten peroxo-complex and TiO2 pre-formed oxide; (III) pre-formed oxides as building blocks. The results showed by electrochemical characterization demonstrated how the electronic parameters (band edge positions, Fermi level energy and charge migration) affect the photocatalytic activity of heterostructures obtained by the distinct synthetic routes. The as-synthesized materials was investigated toward the photodegradation of organic dye (Rhodamine-B) under visible and UV illumination. The growth mechanism was observed to play a significant role in governing surface and interfacial properties, which has a direct influence on xvi materials photoactivity. The band edge positions for the materials was determined from Mott Schottky plot and the experimentally determined energy diagram is consistent with the formation of a type II heterostructure for WO3/TiO2 and it is well correlated to recent reports in literature. As a result, the photogenerated electrons and holes can be spatially distributed in two different crystalline phases in contact and the charge recombination is inhibited, which is efficient for photocatalytic reactions.Additionally, regarding the energy diagram obtained for the heterostrucutres, it is possible from the thermodynamic aspect the use of those structures as promising candidates for the photoelectrocatalytic water splitting, since the band positions are sufficiently large to overcome the character of this reaction.